Effects of Using Digital Magazines "Sobat Busui" Against Mother's Knowledge and Attitudes About Breastfeeding - Alfin Nihayatul Islamiyah; Dina Isfentiani; Dwi Purwanti; Kharisma Kusumaningtyas; Mazlinda Musa (International Journal of Advanced Health Science and Technology, 2024)
Breast milk is best food babies. In this era information technology is developing very rapidly, this brings changes in society. It is possible that breastfeeding mothers also use Android-based media to access information on the internet about breastfeeding. The purpose to analyze the effect of using the digital magazine “Sobat Busui” on mothers’ knowledge and attitudes about breastfeeding. Research method is quantitative research with a Quasi Experiment Design study with one group pre post test design. The independent variable is the use of digital magazines about breastfeeding, the dependent variable is the mother's knowledge and attitudes about breastfeeding. To analyze the effect using the Wilcoxon test. The results showed good knowledge (56.4%) before using the digital magazine “Sobat Busui” after using the digital magazine “Sobat Busui” showing a good increase in knowledge (70.9%) then for a positive attitude (50.9%) before using digital magazine “Sobat Busui” and after using digital magazine “Sobat Busui” showed an increase in positive attitude (67.3%). Wilcoxon test knowledge variable p = 0.006 (< 0.05) and attitude variable p = 0.000 (< 0.05). This means that there is an effect of using the digital magazine “Sobat Busui” on mothers’ knowledge and attitudes. The conclusion is an increase in mothers’ knowledge and attitudes after using the digital magazine “Sobat Busui”. The suggestion is health workers are expected to use the digital magazine “Sobat Busui” as a support in providing health education about breastfeeding and for researchers to add cultural factor variables in future research.